Genetic diversity and population structure of the Black-faced Spoonbill (Platalea minor) among its breeding sites in South Korea: Implication for conservation. (April 2017) - Lee, Mu-Yeong; Kwon, In-Ki; Lee, Kisup; Choi, Sung Kyoung; Jeon, Hey Sook; Lee, Ji-Yeon; Eo, Kyung-yeon; Kim, Hwa-Jung; Kim, Jin-Han; Johnson, Warren E.; Yoo, Jeong-Chil; An, Junghwa
Abstract: The endangered Black-faced Spoonbill Platalea minor has experienced drastic reductions in population size, geographic distribution, and habitat availability throughout East Asia. In the present study, we examined population genetic structure and genetic diversity of Black-faced Spoonbills inhabiting five sites off the west coast of South Korea encompassing a few of its major breeding sites. Ten microsatellite loci and the mitochondrial sequence were used to assess patterns of genetic variation based on 63 individuals. Three ND2 haplotypes were found among 61 individuals; the remaining two were identified as Eurasian Spoonbills, revealing an unexpected hybridization between these two species having different ecological niches in South Korea—the Eurasian Spoonbill overwinters in inland areas, whereas the Black-faced Spoonbill inhabits coastal areas during the summer. Analyses of microsatellite variation revealed no discrete population structure among the five breeding sites but very weak genetic differentiation among geographically distant regions. Assignment tests identified several possible migrants among sites. Our findings suggested that Black-faced Spoonbills from the five breeding sites could be managed as a single population and highlighted the importance of conserving the populations from Maedo, Suhaam, and Namdong reservoir, which are geographically close and have retained high levels of genetic diversity and large populations. Highlights: Ten polymorphic microsatellite loci and the mitochondrial DNA sequence were used to assess genetic diversity and structure. No discrete population structure among the five breeding sites in South Korea but very weak genetic differentiation among geographically distant regions. Black-faced Spoonbill individuals from the five breeding sites could be managed as a single population in South Korea. Unexpected hybridization between the Eurasian Spoonbill and the Black-faced Spoonbill was observed in our genetic studies.